Targeting BAF-perturbed cancers. Issue 12 (December 2018) - Reddy, Divya; Workman, Jerry
BAF is a heterogenous chromatin-remodelling complex, frequently mutated in cancer. A study now defines genome-wide localization patterns of three complexes, cBAF, PBAF and previously unknown ncBAF, and reveals the ncBAF complex as a specific vulnerability in synovial sarcoma and malignant rhabdoid tumours.